THE EFFECT OF AUDIT FEE, AUDIT TENURE AND FIRM SIZE ON AUDIT QUALITY IN FINANCE SECTOR - Yohana, Romaida; Deliana, Deliana; Surianti, Meily; Syahputra, Rizky (Jurnal Riset Terapan Akuntansi, 2025)
The aim of this study is to analyze the relationship between audit fees, audit tenure, and firm size on audit quality in financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research employs secondary data obtained from the official IDX website. Samples were selected using a purposive sampling method, resulting in 65 firms over five years of observation, producing a total of 325 firm-year observations. Data analysis was conducted through logistic regression with the assistance of SPSS version 25. The results indicate that audit fees and audit tenure have a positive impact on audit quality, while firm size has a negative impact. Keywords: Audit Fee, Audit Tenure, Firm Size, Audit Quality.